Pengaruh Transfer Pelatihan, Efikasi Diri, Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Dinas Bina Marga, Cipta Karya Dan Tata Ruang (BMCKTR) Provinsi Sumatera Barat - Anisa Mega Utami; Khairil Aswan (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The aim of this research is to determine whether there is an influence of training transfer, self-efficacy and the non-physical work environment on employee performance at the Department of Highways, Cipta Karya and Spatial Planning of West Sumatra Province. This research uses quantitative methods. The population in this study was 213 and the sample used was 139 using the Slovin formula. The results of this research show that the training transfer variable (X1) has a positive effect on employee performance at the Department of Highways, Cipta Karya and Spatial Planning of West Sumatra Province with a t-count value greater than the t-table (2.456 > 1.97756), with a significance value of moresmaller than the alpha value (0.015 < 0.05), then Ho is rejected and H1 is accepted. The self-efficacy variable (X2) has a positive effect on employee performance at the Department of Highways, Cipta Karya and Spatial Planning of West Sumatra Province with a t-count value greater than the t-table (5.229 > 1.97756), with a significance value smaller than the alpha value (0.000 < 0.05) then Ho is rejected and H2 is accepted. The self-efficacy variable (X3) has a positive effect on employee performance at the Department of Highways, Cipta Karya and Spatial Planning of West Sumatra Province with a t-count value greater than the t-table (2.303 > 1.97756), with a significance value smaller than the alpha value (0.023 < 0.05) then Ho is rejected and H3 is accepted.